Policy options in addressing livestock’s contribution to climate change - P. Gerber; N. Key; F. Portet; H. Steinfeld (Animal, 2010)
There is a great potential to reduce greenhouse gas (GHG) emissions related to livestock production. For achieving this potential will require new initiatives at national and international levels that include promoting research and development on new mitigation technologies; deploying, diffusing and transferring technologies to mitigate emissions; and enhancing capacities to monitor, report and verify emissions from livestock production. This study describes the sources of livestock-related GHG emissions and reviews available mitigation technologies and practices. We assess the main policy instruments available to curb emissions and promote carbon sinks, and discuss the relative merits of alternative approaches. We discuss recent experiences in countries that have enacted mitigation strategies for the livestock sector to illustrate some of the key issues and constraints in policy implementation. Finally, we explore the main issues and challenges surrounding international efforts to mitigate GHG emissions and discuss some possible ways to address these challenges in future climate agreements.